Increased Expression of SHMT2 Is Associated With Poor Prognosis and Advanced Pathological Grade in Oral Squamous Cell Carcinoma - Wu, Zhi-Zhong; Wang, Shuo; Yang, Qi-Chao; Wang, Xiao-Long; Yang, Lei-Lei; Liu, Bing; Sun, Zhi-Jun (Frontiers in Oncology, 2020)
This study focused on the expression of mitochondrial serine hydroxymethyltransferase (SHMT2) in oral squamous cell carcinoma (OSCC) and its correlation with clinical traits and the prognosis of OSCC patients. Immunochemical staining and Western blotting were used to quantify the expression of SHMT2 and related immune markers in OSCC. Using OSCC microarrays and TCGA database, we evaluated the association between SHMT2 and various clinical traits. We found increased expression of SHMT2 was detected in OSCC and correlated with advanced pathological grade and recurrence of OSCC. By a multivariate Cox proportional hazard model, high expression of SHMT2 was shown to indicate a negative prognosis. In addition, in the OSCC microenvironment, increasing the expression of SHMT2 was associated with high expression levels of PD-L1, CMTM6, VISTA, B7-H4, Slug and CD317. In the future, more effort will be required to investigate the role of SHMT2 in the OSCC microenvironment.